2018
DOI: 10.1002/jum.14644
|View full text |Cite
|
Sign up to set email alerts
|

Association between pelvic organ prolapse types and levator‐urethra gap as measured by 3D transperineal ultrasound

Abstract: Bilateral levator ani avulsion as diagnosed by LUG measurements of 25 mm or greater at rest is associated with multicompartment, severe prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…As the most important muscle of the pelvic floor, the LAM is critical for pelvic organ support, leading to POP when defective. Previous studies have found that LAM avulsion bears an association with symptoms of POP and severe prolapse 34,35 and impacts outcomes after prolapse surgery. 36 At 6 weeks after primary prolapse surgery, participants with avulsed (vs intact) LAMs demonstrated worse anterior vaginal support.…”
Section: Discussionmentioning
confidence: 99%
“…As the most important muscle of the pelvic floor, the LAM is critical for pelvic organ support, leading to POP when defective. Previous studies have found that LAM avulsion bears an association with symptoms of POP and severe prolapse 34,35 and impacts outcomes after prolapse surgery. 36 At 6 weeks after primary prolapse surgery, participants with avulsed (vs intact) LAMs demonstrated worse anterior vaginal support.…”
Section: Discussionmentioning
confidence: 99%
“…The levator‐urethra gap (LUG) is the distance between the urethral lumen center and the levator insertion site on the inferior pubic rami. Previous studies evaluating LUG measurements have shown different cutoff values for the LUG 1,10,12‐17 . A cutoff of 2.5 cm has been reported in Australian women, 13 while in Chinese women, the cutoff was 2.365 cm 10 .…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies evaluating LUG measurements have shown different cutoff values for the LUG. 1,10,[12][13][14][15][16][17] A cutoff of 2.5 cm has been reported in Australian women, 13 while in Chinese women, the cutoff was 2.365 cm. 10 It seems that ethnic variation occurs which may question the validity of this cutoff for widespread use.…”
Section: Introductionmentioning
confidence: 96%
“…A kismedencei süllyedéses kórképek kialakulásában a medencefenéki izomzat sérüléseinek vagy strukturális változá sainak kulcsszerepük van. A hüvelyi szülés során bekövetkező traumás elváltozások ultrahangalapú vizsgálatában vezető szerepet játszik a háromdimenziós tomografikus képalkotás [32], azonban Masslo és mtsai munkájából kitűnik, hogy az eddig alkalmazott módszereken felül az UHE a sérülések mellett képes más, funkcióvesztéssel járó állapotok feltárására is, mint a hegképződés vagy a hipokontraktilitás [33]. Xie és mtsai közlése alapján a kismedencei süllyedéses kórképek kialakulásának rizikófaktora lehet a m. levator ani elaszticitásának csökkenése, majd később ugyanezen szerzők bizonyították, hogy az izom elaszticitása mérhetően javul kismedencei torna végzésével [34,35].…”
Section: Ultrahang-elasztográfia a Nőgyógyászatbanunclassified